A rapid LC–MS/MS method for simultaneous determination of berberine and irbesartan in rat plasma: Application to the drug–drug pharmacokinetic interaction study after oral administration in rats. (5th May 2021) - Zhou, Hao; Li, Wenyue; Sun, Ling; Li, Wenfang; Liu, Qian
Abstract: A sensitive, reproducible, and specific liquid chromatography tandem mass spectrometry method was developed and validated to simultaneously determine the concentration of berberine (BBR) and irbesartan in Sprague–Dawley rat plasma, and applied to study the pharmacokinetic drug–drug interaction (DDI) between BBR and irbesartan in rats. In this method, diphenhydramine was used as the internal standard, and the liquid–liquid extraction method using ethyl acetate as the extraction agent was used for sample preparation. After extraction, the prepared samples were run on an Agilent Welchrom C18 column with the mobile phase consisting of methanol–acetonitrile–water solution with 0.5% formic acid (45:50:5, v/v/v) at a flow rate of 0.8 mL·min −1 . The analytes BBR, irbesartan, and diphenhydramine (IS) were detected using multiple reactions monitoring mode, with the ion transitions being m/z 336.1 → m/z 320.0, m/z 429.1 → m/z 206.9, and m/z 256.2 → m/z 167.0, respectively. In the rats' plasma, BBR had good linearity in the range of 0.5–100 ng·mL −1 with the lower limit of quantitation of 0.5 ng·mL −1, and the accuracy, intra‐day, and inter‐day precision were less than 12.33%. Irbesartan had good linearity in the range of 20–1200 ng·mL −1 with the lower limit of quantification of 20 ng·mL −1, and the accuracy, intra‐day, and inter‐day precision were less than 13.55%. The validated method was verified to meet the determination requirements of biological samples. It was the first time to study the pharmacokinetics of DDI between BBR and irbesartan successfully, which would be necessary and beneficial to explore the clinical safety and efficacy of the combination of BBR and irbesartan in the treatment of diabetic nephropathy.